Maternal and Neonatal Complications in Patients With Diminished Ovarian Reserve in In-Vitro Fertilization/Intracytoplasmic Sperm Injection Cycles - Han, Shuang; Zhai, Yiwei; Guo, Qingqing; Qin, Yiming; Liu, Peihao (Frontiers in Endocrinology, 2021)
Background: Diminished ovarian reserve (DOR) is one of the most intractable clinical issues in human reproduction and is reported to be associated with raised risk of recurrent pregnancy loss and aneuploid blastocysts. In this study, we aimed to explore whether DOR was also associated with maternal and neonatal complications in in-vitro fertilization / intracytoplasmic sperm injection cycles. Methods: A retrospective cohort study including women below 40 years of age who achieved singleton live birth after fresh embryo transfer in in-vitro fertilization / intracytoplasmic sperm injection cycles in a single center from January 2012 to June 2019 was conducted. Participants with DOR, defined as basal follicle-stimulating hormone (FSH) ≥ 10IU/L and antimullerian hormone (AMH) < 1.2ng/ml, were enrolled as the study group. The controls were 1:2 matched by age and body mass index with FSH < 10IU/L and AMH ≥ 1.2ng/ml. Maternal and neonatal complications were compared between the DOR group and the controls. Results: A total of 579 women, 193 in the DOR group and 386 matched as controls, were included in this study. Compared to controls, the risk of hypertensive disorders of pregnancy was significantly increased in the DOR group (5.7% vs. 2.1%, P = 0.021). DOR patients also presented slightly higher risks of preterm birth (10.9% vs. 7.5%, P = 0.174) and low birthweight (6.2% vs. 5.4%, P = 0.704) yet without statistical significances. The incidences of gestational diabetes mellitus and placenta previa were comparable between the two groups. Conclusion: Compared to women with normal ovarian reserve, women with diminished ovarian reserve have significantly elevated risk of hypertensive disorders of pregnancy. Therefore, patients with diminished ovarian reserve are supposed to be under more strict antenatal examinations.